STRATEGI PENGEMBANGAN KOPERASI KREDIT (KOPDIT) MEKAR SAI DALAM PEMBIAYAAN AGRIBISNIS DI LAMPUNG - Purba, Moriska N; Affandi, M Irfan; Nugraha, Adia (Lampung University, 2016)
This research aimed to analyze the internal environment of Mekar Sai Credit Cooperative in Lampung Province, analyze the external environment of Mekar Sai Credit Cooperative in Bandar Lampung City and arange development strategy of Mekar Sai Credit Cooperative on agribussiness funding. This research performed with case study method. The respondents in this research were 61 people consist of 10 executives and 51 cooperative members. Data analysis method used in this research was qualitative analysis method. The result of this research showed that cooperative had weakness where the training was not optimally received by the members and was not spread evenly that cause the member to be lack of concern and being inactive towards cooperative and had threat in more competitive busniess competition. Priority strategy that can be used in development and sustainable of Mekar Sai Credit Cooperative were (a) optimalize training and education for members evenly so the members could be more concern towards cooperative development, (b) using excecutive’s duty in managing cooperative democratically to take society’s attention that were not members, (c) using cooperative capital effectively to keep finance stability. Key words: credit cooperative, development strategic, SWOT